2015
DOI: 10.1002/uog.14776
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal shape of the cavum septi pellucidi: an indirect sign of partial agenesis of the corpus callosum

Abstract: Objective To describe and assess the presence of a new indirect sign of partial agenesis of the corpus callosum (pACC): an abnormally shaped cavum septi pellucidi (CSP). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 16 publications
4
38
0
Order By: Relevance
“…Diagnosing SCC is challenging. Many previous studies suggested various diagnostic tools in an attempt to confront this problem . There are several reference charts for assessing CC biometrics according to gestational age .…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosing SCC is challenging. Many previous studies suggested various diagnostic tools in an attempt to confront this problem . There are several reference charts for assessing CC biometrics according to gestational age .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some authors have suggested that an abnormally shaped CSP may be a valid indirect sign of pACC . Shen has proposed that CSP shape be included as a new indirect sign, having found an abnormally shaped CSP in 52% of isolated pACC occurrences with no customary indirect signs.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, approximately one‐third of isolated pACC defects carry the potential for some degree of neurologic morbidity, thus highlighting the need to identify this anomaly. In recent years, some authors have suggested that an abnormally shaped CSP may be a valid indirect sign of pACC . The aim of this study was to evaluate the performance of indirect sonographic signs in detecting pACC at midgestation, using the CSP ratio as a new indirect finding.…”
Section: Introductionmentioning
confidence: 99%
“…A CSP with a large width may indicate an increased risk of numeric or structural chromosomal abnormality . An abnormal ratio of the CSP length and width is considered to be an indirect sign of partial agenesis of the corpus callosum (pACC) . However, different studies have used different techniques and planes to measure the CSP.…”
Section: Introductionmentioning
confidence: 99%